ANALYSIS OF FUEL STATIONS HAZARDS BY USING RISK ASSESSMENT CRITERIA - Mirza, Munir (2010)
performances can be achieved only if safety matters priority at all stages of project addressed adequately. Concrete efforts of owners, contractors, sub contractors and designers are equally important at different levels of project. It is necessary to develop such strategies that can help to reduce injury cases. Past safety studies investigated various methods to improve injury statistics but it still contains more room for improvement. This paper will present the application of risk assessment criteria (RAC) to identify critical, major, moderate and minor activities during fuel station operation. Health safety & environmental hazards related to fuel stations activities will be identified, estimate the associated risks and necessary control measures for mitigation of identified risks will be highlighted in this study. The RAC used in this study is widely applying in upstream oil and gas sector in Pakistan. Poor maintenance, carelessness, house keeping, mechanical fault and robbery found to be the major causes of occurrences of unsafe acts and unsafe conditions at fuel stations. RAC are methods of work system design and helpful to address associated risks in a project. During study it was felt that many resources are available within an organization to minimize accidents/injuries but due to not fully utilization of these resources accidents/incidents happen. After calculating risks, application of available resources can be done more appropriately. In case of unavailability, requirements can be highlighted and applied strategically to get better results.